Parenting Styles in the Psychosocial Development of Children from Early Childhood to Adolescence: A Literature review - Nirmalasari, Rut; Setija Utami, Sih; Widyo Hastuti, Lita (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The psychosocial development of children and adolescents is a crucial factor that parents need to consider. Parental parenting styles significantly impact the guidance of a child's development at every stage. This study aims to examine the importance of parental parenting styles in accompanying the psychosocial development stages of children, from early childhood (age 3) through late adolescence (age 18). This literature analysis combines Baumrind’s theory of parenting styles with Erik Erikson’s theory of psychosocial development. According to Baumrind, there are three primary parental parenting styles: authoritarian, democratic (authoritative), and permissive. Within Erik Erikson’s psychosocial development, these stages of child and adolescent development still require the parents' presence in guiding and providing attention to the children. The method used in this research is a literature review. The data collection process was carried out through a search on Google Scholar. Out of 25 journals published between 2020 and 2025, 20 were found to be relevant to the theme. The journal search focused exclusively on parenting styles and the psychosocial development of children and adolescents. The results of the literature review indicate that the democratic (authoritative) parenting style is a better form of parenting for the psychosocial development of children and adolescents compared to the authoritarian style. Other discovered parenting styles included responsive and adaptive parenting.Perkembangan Psikososial anak dan remaja merupakan salah satu faktor penting yang perlu diperhatikan oleh orang tua. Gaya pola pengasuhan orang tua memberikan dampak dalam pendampingan perkembangan anak di setiap tahapannya. Penelitian ini bertujuan untuk melihat pentingnya gaya pola asuh orang tua dalam mendampingi tahapan perkembangan psikosoial anak-anak usia dini 3 tahun hingga usia remaja akhir 18 tahun. Analisis literatur ini menggabungkan gaya pola pengasuhan teori Baumrind dengan teori perkembangan Psikososial Erik Erikson. Menurut Baumrind ada tiga gaya pola pengasuhan orang tua yaitu pola asuh otoriter, demoktatif dan permisif. Pada perkembangan psikososial Erik Erikson, tahapan perkembangan anak-anak dan remaja yang masih membutuhkan kehadiran orang tua dalam mendampingi dan memberikan perhatian kepada anak-anak. Metode yang digunakan dalam penelitian ini adalah literature review. Proses pengumpulan data dilakukan melalui pencarian Google Scholar. Sebanyak 25 jurnal yang diterbitkan pada tahun 2020-2025 didapatkan hasil 20 jurnal yang relevan dengan tema. Pencarian jurnal hanya berfokus pada gaya pola asuh dan perkembangan psikososial anak dan remaja. Hasil literature review menunjukkan gaya pola asuh demokratis merupakan gaya pengasuhan yang baik bagi perkembangan psikosial anak dan remaja dibandingkan dengan gaya pola asuh otoriter. Penemuan gaya pola asuh yang lain yaitu pola asuh responsif dan adaptif.